"I know your intention is good, but I still feel bad": Cultural divergence and convergence in the effect of leader's angry feedback. Issue 8 (29th January 2020) - Shao, Bo; Martin, Lee
Abstract : Purpose: Drawing on a contagion-interpretation model of leader affective displays and leader effectiveness, the purpose of this paper is to examine the effects of leaders' angry feedback on followers' cognitive and affective reactions, and ultimately, perceived leader effectiveness across different cultural contexts. Design/methodology/approach: In this paper, two experimental studies were conducted with a total of 528 participants. Findings: The results revealed a culturally divergent cognitive effect: in Western cultures where vertical collectivism is low, leaders' angry feedback reduced followers' inferred developmental intention and subsequently, perceived leader effectiveness, whereas in East Asian cultures where vertical collectivism is high, leaders' angry feedback reduced the two variables to a lesser extent or did not have any effect. In contrast, there was a culturally convergent emotional effect: the impact of leaders' angry feedback on followers' negative emotions and subsequently, perceived leader effectiveness was the same, regardless of the level of vertical collectivism. Originality/value: This research is the first to demonstrate that culture – in particular, the dimension of vertical collectivism – has different impacts on the two mechanisms (i.e. cognitive and affective) through which leader's angry feedback influences followers' perceived leader effectiveness.